2014
DOI: 10.6061/clinics/2014(04)03
|View full text |Cite
|
Sign up to set email alerts
|

Effect of minimally invasive percutaneous plates versus interlocking intramedullary nailing in tibial shaft treatment for fractures in adults: A meta-analysis

Abstract: OBJECTIVE:The aim of this article was to determine the effects of minimally invasive percutaneous plates versus interlocking intramedullary nailing in the treatment of tibial shaft fractures in adults.METHOD:Literature searches of the Cochrane Library, PubMed, EMBASE, the Chinese Biomedical Literature database, the CNKI database, Wanfang Data, and the Weipu Journal database were performed up to August 2013. Only randomized and quasi-randomized controlled clinical trials comparing the use of percutaneous plates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…The time duration from injury to surgery also plays a major role in bringing the patient to early mobilization and near normal function [8,[16][17][18] . Timing of surgery when the tissues are least oedematous ensures better outcome in terms of soft tissue healing, fracture healing and early mobilization without any complications like knee stiffness [19,20] . In our study, patients operated within 5-7 days of injury came up with excellent results when compared to patients operated after one week.…”
Section: Discussionmentioning
confidence: 99%
“…The time duration from injury to surgery also plays a major role in bringing the patient to early mobilization and near normal function [8,[16][17][18] . Timing of surgery when the tissues are least oedematous ensures better outcome in terms of soft tissue healing, fracture healing and early mobilization without any complications like knee stiffness [19,20] . In our study, patients operated within 5-7 days of injury came up with excellent results when compared to patients operated after one week.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors like Hasenboehler et al 26 have shown favorable results from the use of plates in distal tibial fractures where intramedullary nailing was contraindicated. He et al 27 reviewed 11 publications in a meta-analysis comparing the use of intramedullary nails with percutaneous plating in diaphyseal tibial fractures and found no significant differences in the outcomes between these two methods.…”
Section: Discussionmentioning
confidence: 99%
“…El tiempo de reparación del mismo tipo de fracturas con la utilización de diferentes tipos de material de osteosíntesis genera divergencia en la reparación. Por ejemplo, las fracturas de fémur reparadas con clavos canulados y lisos varían en promedio 6 semanas, situación que no ocurre con el uso de placas percutáneas mínimamente invasivas versus clavos intramedulares enclavados en el tratamiento de las fracturas de la diáfisis tibial en adultos [65], técnica que adicionalmente puede tener otro tipo de beneficios.…”
Section: Impacto De Las Nuevas Tecnologías En La Reparación De Las Leunclassified